Renderment Of Fresh Milkfish Skin Collagen (Chanos Chanos) Resulting From Acetic Acid Extraction - Paudi, Riskal; Sulistijowati, Rieny; Mile, Lukman (Universitas Negeri Gorontalo, 2020)
This study aims to determine the collagen yield of milk fish skin (Chanos chanos) extracted by acetic acid. The method used in this study is the kuantitative observation of acetic acid concentration were 0.3; 0.5; and 0.7M, and performed three times. Analysis of yield data using quantitative descriptive. Analysis Results Concentration yields of 0.3; 0.5; and 0.7M were1.27%, 1.56% and 1.84% yields. The results of milk fish collagen yield showed that the treatment of using acetic acid 0.7M to produce collagen yield approached the standard SNI collagen.